2018
DOI: 10.1002/phar.2116
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Outpatient Rabbit Antithymocyte Globulin Induction Therapy Administration in Kidney Transplant Recipients

Abstract: Outpatient administration of rATG is feasible, safe, and did not increase readmissions in the period directly following administration. The findings of this analysis support our continued use of the outpatient rATG protocol at our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Some providers have asked about incorporating G-CSF administration to assist with WBC count recovery during administration of T-cell depleting therapy such as r-ATG, though there is no organ transplant literature to support this practice. We do not advocate for this practice at our center given the availability to delay r-ATG administration to the outpatient setting, which allows for recovery from cytopenia-related adverse events between doses without compromising efficacy 24. A previous study by Stevens et al25 suggested that failure to appropriately adjust VGCV dosing based on renal function may contribute to the risk of leukopenia in kidney transplant recipients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some providers have asked about incorporating G-CSF administration to assist with WBC count recovery during administration of T-cell depleting therapy such as r-ATG, though there is no organ transplant literature to support this practice. We do not advocate for this practice at our center given the availability to delay r-ATG administration to the outpatient setting, which allows for recovery from cytopenia-related adverse events between doses without compromising efficacy 24. A previous study by Stevens et al25 suggested that failure to appropriately adjust VGCV dosing based on renal function may contribute to the risk of leukopenia in kidney transplant recipients.…”
mentioning
confidence: 99%
“…About half of our patients had their prednisone dose slightly increased concomitant with decreases in their antimetabolite. We do not advocate for this practice at our center given the availability to delay r-ATG administration to the outpatient setting, which allows for recovery from cytopenia-related adverse events between doses without compromising efficacy 24. Notably, 97.2% of our study population received at least one dose of r-ATG for induction immunosuppression.…”
mentioning
confidence: 99%
“…33,[41][42][43] Compared with central administration, peripheral administration of rATG offers several advantages by avoiding central catheter placement and associated complications and facilitating outpatient administration. 26,44,45 Peripheral administration of rATG has been shown to be safe and effective when administered in the ambulatory setting without increased rates of readmissions and resulting in significant reduction in hospital length of stay. 42,45 Infusion time is the major limitation to this strategy.…”
Section: Peripheral and Outpatient Ratg Administrationmentioning
confidence: 99%
“…26,44,45 Peripheral administration of rATG has been shown to be safe and effective when administered in the ambulatory setting without increased rates of readmissions and resulting in significant reduction in hospital length of stay. 42,45 Infusion time is the major limitation to this strategy. While outpatient administration has not been studied in the setting of rejection treatment, the benefits in this population would theoretically be more substantial, given the higher cumulative dose for this indication and lack of need for inpatient surgical recovery.…”
Section: Peripheral and Outpatient Ratg Administrationmentioning
confidence: 99%